ANALYSIS OF THE EFFECTIVENESS OF MARKETING COMMUNICATIONS MULTIPURPOSE CREDIT PRODUCT PURCHASE DECISION THROUGH BRAND IMAGE AT PT.BANK SUMUT MEDAN MELATI BRANCH - Hefmi Dewi Siahaan; Endang Suilistya Rini; Fadli (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
Intense competition makes it increasingly difficult for banks to increase the number of customers in their efforts to maintain and increase their market share. So the banks have to work hard to stay competitive,namely through improving customer marketing communications and strengthening brand image. The aims of the research are, 1) To analyze the influence of marketing communications on purchasing decisions for Multipurpose Credit products at PT Bank Sumut Melati Medan Branch, 2) To analyze marketing communications affect the brand image of Multipurpose Credit products at PT Bank Sumut Melati Branch Medan. To analyze the influence of brand image on the decision to purchase Multipurpose Loan products at PT Bank Sumut Melati Medan Branch, 3) To analyze marketing communications affect the purchasing decision of Multipurpose Loan products through brand image at PT Bank Sumut Melati Medan Branch. This research is a descriptive type research with a quantitative approach. The population in this study is 64 people who use Multipurpose Credit products in 2020. Because the population size is very limited, this study did not use a sample, directly observing the population. Based on the hypothesis that has been formulated, all data is processed using the SEM-PLS analysis technique using SmartPLS 3.0 software. Based on the results of the test, it was found that marketing communication variables and brand image have a significant effect on purchasing decisions.